THE EFFECTIVITY OF SCAFFOLD FROM ANADARA GRANOSA SHELL-STICHOPUS HERMANNI ON BLOOD VESSEL COUNTS AFTER TOOTH EXTRACTION - Rima Parwati Sari; Chaterina Dyah Nanik Kusumawardani; Retno Pudji Rahayu; Sri Agoes Soedjarwo; Dian Widya Damaiyanti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Alveolar bone resorption can occur after tooth extraction. One source of bone scaffold material is hydroxyapatite and tricalcium phosphate (HA-TCP). The shell of Anadara granosa can be synthesized to be HA-TCP. Hyaluronic acid, which is widely contained in Stichopus hermanni, can stimulate endothelial progenitor cells for the healing process. Purpose: This research aims to prove the Effectivity of scaffold from Anadara granosa shell-Stichopus hermanni on blood vessel counts after tooth extraction. Methods: The sample in this study was male Wistar rats divided into four study groups randomly. Each group consists of 6 rats. Extraction was carried out on the mandibular first incisor, then was given gelatin as a placebo in the control group, treatment groups given scaffold from Anadara granosa shells (AG), and scaffold combination from Anadara granosa shells-Stichopus hermanni with concentrations of 0.4%-0.8%. (AGSH1-AGSH2). Development of HA-TCP synthesized from Anadara granosa combined with Stichopus hermanni extract for biomedical scaffolds using the freeze-dried method. Observations were made three days after tooth extraction. Data analysis has used one-way ANOVA followed by Tukey HSD (p<0.05). Results: The results of the ANOVA test followed by the HSD-Tukey test showed a significant difference between C (7.33±1.51) and AGSH1 (11.50±1.38), AGSH2 (21.17±1.94), AG (9.33±1.63) and AGSH1 with AGSH2, but between AG and, AGSH1 no significant differences.Conclusions: Combination scaffold from Anadara granosa shell and Stichopus hermanni 0.8% effectively increased blood vessel counts after tooth extraction.